Penguatan Akhlak Mulia dalam Pembelajaran Tahfidz Al-Qur’an di MTs Ma’arif Binjai Hulu Sintang (Perspektif Rekonstruksi Sosial) - Sukino, Sukino Sukino; Muttaqin, Imron Imron (Ta'allum: Jurnal Pendidikan Islam, 2019)
This research is motivated by parents' concern for the morality of teenagers in their lives, until now teenagers in various villages show attitudes that are not in accordance with Islamic religious values ​​and norms in society. The actions of teenagers that lead to free sex, crime, and bullying are increasingly difficult for parents to control, as is the case in the Binjai Hulu Sintang district. However, in the last three years there have been Islamic education institutions which have a significant effect on adolescent moral change in Binjai Hulu. The purpose of this study: first to explain the model of student moral reinforcement in Tahfidz Qur'an learning; secondly changes in the noble character of students in the perspective of parents and the surrounding community. This research is a qualitative research with a phenomenological approach. The research data was collected using interviews and observations, the results showed that (1) the model of noble moral reinforcement in Tahfidz Quran learning relies on the meaning of the verse contextually, the social construction approach in the process of internalizing noble moral values, knowledge construction through the use of time and space dimensions. (2) Significant changes in student morals after participating in the Tahfidz Quran activities at MTs Ma'arif 2 Binjai Hulu are consistency in worship, courtesy in communication, and good self-control. The findings of this study have implications for the enrichment of concepts and practical skills in developing students' noble attitudes (noble morals) in the formal education environment